Acute abdomen with adnexal masses in the reproductive age group: diagnosis and management - Murki, Anuradha D.; Kamineni, Vasundhara; Velagapudi, Sowmya R.; Deshpande, Ashok K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Women with adnexal masses can present with acute symptoms such as abdominal pain, nausea and vomiting. As there is insufficient evidence on the frequency, presentation and management of adnexal masses we conducted this study to evaluate the clinical profile, surgical findings and histopathology of adnexal masses in women presenting with acute abdomen and needing surgical intervention. Methods: In this prospective observational study, history, examination, investigations and ultrasound of abdomen and pelvis were evaluated in women presenting with acute abdomen with adnexal mass and needing surgical intervention. Diagnosis was confirmed from the operative findings and histopathology. Etiology and its correlation with clinical symptoms and signs and radiological diagnosis formed the primary objective of the study. Results: Of the 79 patients enrolled in the study, the mean age was 30.82±6.69 years. Younger women were likely to have ectopic pregnancy while older women (>35 years) other tubal pathologies. Pain abdomen (n=70) and nausea (n=53), bleeding per vagina(n=33), menstrual irregularities (n=18), fever (n=10) abdominal distension (n=10) and dysuria (4) were the common symptoms. Etiology of the adnexal mass was ectopic pregnancy (57%), ovarian mass (34%), tubal mass (7.5%), tube and ovary (2.5%) in 46, 25, 6 and 2 patients respectively. 61% (n=48) of the women underwent laparoscopic management. Women with ruptured ectopic pregnancy were more likely to have abdominal distension, pallor, hypotension, cervical motion tenderness and need for blood transfusions. Conclusions: In women from reproductive age group with adnexal mass and needing surgery, ectopic pregnancies and benign ovarian tumours were the common etiologies. Urine pregnancy test and ultrasound are useful tests to differentiate ectopic from ovarian and tubal pathology.